Modeling of Carbon Redistribution and Tetragonality Evolution in Supersaturated Ferrite - Svoboda, J.; Ressel, G.; Brandl, D. (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2024)
Martensite and bainite are formed from austenite through the rapid application of Bain’s strain. In several studies, martensite is considered as a body-centered tetragonal phase, but it can also be viewed as bcc ferrite supersaturated with carbon, subject to internal residual stresses from incomplete relaxation of Bain’s strain. Recent electron backscatter diffraction measurements have revealed a broad spectrum of tetragonality in quenched martensite, which can be attributed to the diversity of internal stress rather than variations in carbon distribution. Therefore, a thermodynamic unit cell model is developed to calculate the kinetics of carbon atom occupancy in particular kinds of octahedral interstitial lattice sites, contributing to tetragonality in loaded ferrite. The model includes a Zener-ordering term that influences carbon atom distribution and consequently affects tetragonality. Simulations suggest that carbon redistribution among octahedral interstitial lattice sites reaches equilibrium with internal stress within an hour at room temperature. The presented model provides a framework for understanding tetragonality in martensite and bainite, incorporating the effects of internal stress and carbon atom distribution in particular kinds of octahedral interstitial lattice sites.